Measurement of the branching fractions B(B0 → p[bar]pp[bar]p) and B(B0s → p[bar]pp[bar]p) - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2023)
Searches for the rare hadronic decays B0→p¯pp¯p and B0s→p¯pp¯p are performed using proton-proton collision data recorded by the LHCb experiment and corresponding to an integrated luminosity of 9 fb−1. Significances of 9.3σ and 4.0σ, including statistical and systematic uncertainties, are obtained for the B0→p¯pp¯p and B0s→p¯pp¯p signals, respectively. The branching fractions are measured relative to the topologically similar normalization decays B0→J/ψ(→p¯p)K*0(→K+π−) and B0s→J/ψ(→p¯p) ϕ(→K+K−). The branching fractions are measured to be B(B0→p¯pp¯p)=(2.2±0.4±0.1±0.1)×10−8 and B(B0s→p¯pp¯p)=(2.3±1.0±0.2±0.1)×10−8. In these measurements, the first uncertainty is statistical, the second is systematic, and the third one is due to the external branching fraction of the normalization channel.